Manufacturing strategies in different environments: does equifinality or a dominant strategy exist?. (2017) - Cai, Shaohan
This study addresses two essential issues related to equifinality: (1) whether firms can choose different but equally effective manufacturing strategies for different environments (equifinality) and (2) whether there is one strategy adopted by more firms than others (dominant strategy) in each individual environment. With data collected from 434 Chinese manufacturing companies, this study identifies a four-cluster taxonomy of business environments (harsh, labour munificent, stable and low-cost) and a four-cluster taxonomy of manufacturing strategies (mass servers, marketeers, manufacturing emphasisers and low emphasisers). The analyses show that dynamism and munificence exert joint effects on equifinality and the existence of a dominant strategy.